Review of oral oxymorphone in the management of pain - Paul Sloan (Dove Medical Press, 2008)
Paul SloanUniversity of Kentucky Medical Center, Department of Anesthesiology, Lexington, KY, USAAbstract: Chronic cancer and nonmalignant pain (CNMP) is a common and major health problem afflicting approximately 40 million persons in the US. Most cancer patients, and many patients with CNMP, require opioid analgesics to obtain adequate pain relief. Oral oxymorphone is a new formulation of an existing parenteral opioid that has become available for the treatment of significant pain: acute postoperative, chronic arthritis, chronic low back, and chronic cancer pain. Oxymorphone is a typical mu-opioid agonist that is effective in both immediate- and extended-release (IR and ER) formulations. Oxymorphone is more lipid soluble than morphine, resulting in a rapid onset of action when given in tablet formulation, with a duration of action of approximately 4–6 hours in IR and 12 hours in ER preparations. Oxymorphone provides excellent pain relief for significant pain, with typical opioid side effects that are usually mild or moderate in intensity. Multiple double-blind, prospective, placebo-controlled clinical trials have demonstrated the clinical efficacy and safety of this new oral opioid preparation. Oral oxymorphone is an effective opioid that provides a new therapeutic option for the physician.Keywords: chronic pain, oxymorphone, opioids, extended-release, sustained-release, cancer pain